Multiple Proteins of Lacticaseibacillus rhamnosus GG Are Involved in the Protection of Keratinocytes From the Toxic Effects of Staphylococcus aureus - El-Chami, Cecile; Choudhury, Rawshan; Mohammedsaeed, Walaa; McBain, Andrew J.; Kainulainen, Veera; Lebeer, Sarah; Satokari, Reetta; O’Neill, Catherine A. (Frontiers in Microbiology, 2022)
We have previously shown that lysates of Lacticaseibacillus rhamnosus GG confer protection to human keratinocytes against Staphylococcus aureus. L. rhamnosus GG inhibits the growth of S. aureus as well as competitively excludes and displaces the pathogen from keratinocytes. In this study, we have specifically investigated the anti-adhesive action. We have tested the hypothesis that this activity is due to quenching of S. aureus binding sites on keratinocytes by molecules within the Lacticaseibacillus lysate. Trypsinisation or heat treatment removed the protective effect of the lysate suggesting the involvement of proteins as effector molecules. Column separation of the lysate and analysis of discrete fractions in adhesion assays identified a fraction of moderate hydrophobicity that possessed all anti-adhesive functions. Immunoblotting demonstrated that this fraction contained the pilus protein, SpaC. Recombinant SpaC inhibited staphylococcal adhesion to keratinocytes in a dose-dependent manner and improved keratinocyte viability following challenge with viable S. aureus. However, SpaC did not confer the full anti-adhesive effects of the LGG lysate and excluded but did not displace S. aureus from keratinocytes. Further purification produced four protein-containing peaks (F1-F4). Of these, F4, which had the greatest column retention time, was the most efficacious in anti-staphylococcal adhesion and keratinocyte viability assays. Identification of proteins by mass spectrometry showed F4 to contain several known ‘moonlighting proteins’ – i.e. with additional activities to the canonical function, including enolase, Triosephosphate isomerase (TPI), Glyceraldehyde 3 phosphate dehydrogenase (G3P) and Elongation factor TU (EF-Tu). Off these, only enolase and TPI inhibited S. aureus adhesion and protected keratinocytes viability in a dose dependent manner. These data suggest that inhibition of staphylococcal binding by the L. rhamnosus GG lysate is mediated by SpaC and specific moonlight proteins.